The Digestive Enzymes in the Larvae of Chaoborus obscuripes van der Wulp, 1867. - Chowdhury, S. H. (Contributions to Entomology = Beiträge zur Entomologie, 1970)
The present paper reports the findings of a study of nine different enzymes produced by the mid-gut of Chaoborus obscuripes larvae in relation to feeding. Of the enzymes studied proteinase, amylase and acid and alkaline phosphatases were found in the mid-gut cavity and mid-gut tissue of fed as well as starved larvae. Invertase and maltase were detected in the mid-gut tissue of both fed and starved larvae, but never in the tropic cavity. Dipeptidase was detected in the mid-gut cavity and mid-gut tissue of fed larvae only. Lactase and lipase (capable of breaking down olive oil and sunflower seed oil) were found to be absent. The author concludes that the predacious habit has not caused a reduction of the carbohydrate digesting enzymes and that a ferment-chain system is operating in these larvae whereby a series of enzymes, in succession, break down the complex food substances step by step.